Vocational education and other activities at Dubnica Institute of Technology in Dubnica nad Váhom - LAJČIN, Daniel; SLÁVIKOVÁ, Gabriela; VÁRKOLY, Ladislav (Journal of Education, Technology and Computer Science, 2014)
The article focuses on Dubnica Institute of Technology in Dubnica nadVáhom activities in the field of vocational higher education. It informs of theorganizational structure of Dubnica Institute of Technology in Dubnica nadVáhom and study programs offer. Other Dubnica Institute of Technology inDubnica nad Váhom activities are University of the third age, Children’s University,Student research training activities (ŠVOČ) and some others. DTI publishesscientific journal Acta Technologica Dubnicae. Dubnica Institute of Technologyin Dubnica nad Váhom was awarded an ISO quality certificate, that confirmed,the management system fulfils the requirements of ISO 9001: 2008 atDubnica Institute of Technology in Dubnica nad Váhom.